Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1161/strokeaha.113.002999
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density and Incidence of Stroke

Abstract: Background and Purpose-The prospective link between osteoporosis and future risk of stroke requires evidence from large-scale population-based long-term studies. Methods-Calcaneum broadband ultrasound attenuation was measured in the Norfolk cohort of the European Prospective Investigation into Cancer-Norfolk between 1997 and 2000. Incident strokes were ascertained by hospital record linkage and death certificates in March 2009 and December 2011, respectively. A search of MEDLINE and EMBASE was performed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 42 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…Furthermore, Moayyeri et al observed a similar performance between BUA and DEXA measures in prediction of long-term fractures risk in the elderly [ 43 ]. Overall, these findings suggest that BUA can be used as a valid, inexpensive, easy, and quick alternative assessment tool for bone health, and most importantly, without radiation [ 1 , 44 ]. The os calcis is a weight-bearing bone [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Moayyeri et al observed a similar performance between BUA and DEXA measures in prediction of long-term fractures risk in the elderly [ 43 ]. Overall, these findings suggest that BUA can be used as a valid, inexpensive, easy, and quick alternative assessment tool for bone health, and most importantly, without radiation [ 1 , 44 ]. The os calcis is a weight-bearing bone [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study on osteoporosis revealed that low bone density in femoral neck and osteoporosis would result in increasing stroke risks and mortality (14). A prospective study by European researchers also showed that osteoporosis may directly increase the incidence of stroke (15). All of these studies have suggested that stroke and osteoporosis were in reciprocal causation.…”
Section: Discussionmentioning
confidence: 99%
“…Low BMD has been associated with a higher stroke risk in later life, meaning the stroke patient might already be predisposed to a higher fracture risk for reasons that are not entirely understood, but may involve shared risk factors for vascular calcification [ 67 ]. What is clear, however, is that there is a rapid and substantial decline in BMD following an acute stroke, as is the case following spinal cord injury and as seen in astronauts [ 57 ].…”
Section: Bone Mineral Density (Bmd) Reductionmentioning
confidence: 99%